IMPOSSIBLE SPAWNING GROUND OF POLYDACTYLUS INDICUS (SHAW) NEAR BOMBAY - Kagwade, P V (Indian Journal of Fisheries, 2011)
From the mature specimens of Polydactylus indicus collected at Dahanu,a fishing village north of Bombay, it seems that the fish spawns in the inshorewater. The earlier two records of the spawning grounds are from the Gulf ofKutch and the inshore waters of Madras.